Intraoperative Hyperoxia Does Not Reduce Postoperative Pain: Subanalysis of an Alternating Cohort Trial. (June 2019) - Cohen, Barak; Ahuja, Sanchit; Schacham, Yehoshua N.; Chelnick, David; Mao, Guangmei; Ali-Sakr Esa, Wael; Maheshwari, Kamal; Sessler, Daniel I.; Turan, Alparslan
Abstract : BACKGROUND: Postoperative pain is common and promotes opioid use. Surgical wounds are hypoxic because normal perfusion is impaired. Local wound ischemia and acidosis promote incisional pain. Some evidence suggests that improving oxygen supply to surgical wounds might reduce pain. We therefore tested the hypothesis that supplemental (80% inspired) intraoperative oxygen reduces postoperative pain and opioid consumption. METHODS: We conducted a post hoc analysis of a large, single-center alternating cohort trial allocating surgical patients having general anesthesia for colorectal surgery to either 30% or 80% intraoperative oxygen concentration in 2-week blocks for a total of 39 months. Irrespective of allocation, patients were given sufficient oxygen to maintain saturation ≥95%. Patients who had regional anesthesia or nerve blocks were excluded. The primary outcome was pain and opioid consumption during the initial 2 postoperative hours, analyzed jointly. The secondary outcome was pain and opioid consumption over the subsequent 24 postoperative hours. Subgroup analyses of the primary outcome were conducted for open versus laparoscopic procedures and for patients with versus without chronic pain. RESULTS: A total of 4702 cases were eligible for analysis: 2415 were assigned to 80% oxygen and 2287 to 30% oxygen. The groups were well balanced on potential confounding factors. Average pain scores and opioid consumption were similar between the groups (mean difference in pain scores, −0.01 [97.5% CI, −0.16 to 0.14; P = .45], median difference in opioid consumption, 0.0 [97.5% CI, 0 to 0] mg morphine equivalents; P = .82). There were also no significant differences in the secondary outcome or subgroup analyses. CONCLUSIONS: Supplemental intraoperative oxygen does not reduce acute postoperative pain or reduce opioid consumption.